A glimpse of undiscovered insect diversity: A collection of 150 new taxa of insects (cover) - Anderson, R.; Bickel, D. J.; Brown, J. W.; Buffington, M.; Fery, H.; Forrester, J.; Gall, L. F.; Gilka, W.; Johnson, K.; Kondratieff, B. C.; Klimaszewski, J.; Majka, C.; et al. (Zootaxa, 2012)
-